2021
DOI: 10.1016/j.jbo.2021.100392
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA KRT8P41/miR-193a-3p/FUBP1 axis modulates the proliferation and invasion of chordoma cells

Abstract: Highlights lncRNA KRT8P41 potentially serves as an oncogenic lncRNA in chordoma. miR-193a binds to lncRNA KRT8P41 and FUBP1 3′UTR. LncRNA KRT8P41/miR-193a axis modulates chordoma cell aggressiveness through FUBP1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Two studies were multicenter, which includes different populations, increasing the strength of the study ( 21 , 34 ). With regard to study design, 5 studies were prospective (7.3%) ( 26 , 35 38 ) and 63 studies were retrospective (92.7%) ( 21 25 , 27 34 , 39 – 87 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were multicenter, which includes different populations, increasing the strength of the study ( 21 , 34 ). With regard to study design, 5 studies were prospective (7.3%) ( 26 , 35 38 ) and 63 studies were retrospective (92.7%) ( 21 25 , 27 34 , 39 – 87 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, LOC554202 may play an anti-tumor role in chordoma via suppressing proliferation and invasion of chordoma cells [12] . LncRNA KRT8P41 acted as a tumor promoter via accelerating chordoma cell proliferation and invasion [13] . In addition, the former report indicated that lncRNA X-inactive specific transcript (XIST) was upregulated in chordoma, which might promote the development of chordoma [14] .…”
Section: Introductionmentioning
confidence: 99%